Development of Equine IgG Antivenoms against Major Snake Groups in Mozambique. - Felipe Raimondi Guidolin; Celso Pereira Caricati; José Roberto Marcelino; Wilmar Dias da Silva (Public Library of Science (PLoS), 2016)
BACKGROUND:Snake envenoming is a significant public health problem in underdeveloped and developing countries. In sub-Saharan Africa, it is estimated that 90,000-400,000 envenomations occur each year, resulting in 3,500-32,000 deaths. Envenomings are caused by snakes from the Viperidae (Bitis spp. and Echis spp.) and Elapidae (Naja spp. and Dendroaspis spp.) families. The African continent has been suffering from a severe antivenom crisis and current antivenom production is only sufficient to treat 25% of snakebite cases. Our aim is to develop high-quality antivenoms against the main snake species found in Mozambique. METHODS:Adult horses primed with the indicated venoms were divided into 5 groups (B. arietans; B. nasicornis + B. rhinoceros; N. melanoleuca; N. mossambica; N. annulifera + D. polylepis + D. angusticeps) and reimmunized two times for antivenom production. Blood was collected, and plasma was separated and subjected to antibody purification using caprylic acid. Plasmas and antivenoms were subject to titration, affinity determination, cross-recognition assays and in vivo venom lethality neutralization. A commercial anti-Crotalic antivenom was used for comparison. RESULTS:The purified antivenoms exhibited high titers against B. arietans, B. nasicornis and B. rhinoceros (5.18 x 106, 3.60 x 106 and 3.50 x 106 U-E/mL, respectively) and N. melanoleuca, N. mossambica and N. annulifera (7.41 x 106, 3.07 x 106 and 2.60 x 106 U-E/mL, respectively), but lower titers against the D. angusticeps and D. polylepis (1.87 x 106 and 1.67 x 106 U-E/mL). All the groups, except anti-N. melanoleuca, showed significant differences from the anti-Crotalic antivenom (7.55 x 106 U-E/mL). The affinity index of all the groups was high, ranging from 31% to 45%. Cross-recognition assays showed the recognition of proteins with similar molecular weight in the venoms and may indicate the possibility of paraspecific neutralization. The three monospecific antivenoms were able to provide in vivo protection. CONCLUSION:Our results indicate that the anti-Bitis and anti-Naja antivenoms developed would be useful for treating snakebite envenomations in Mozambique, although their effectiveness should to be increased. We propose instead the development of monospecific antivenoms, which would serve as the basis for two polyvalent antivenoms, the anti-Bitis and anti-Elapidae. Polyvalent antivenoms represent an increase in treatment quality, as they have a wider range of application and are easier to distribute and administer to snake envenoming victims.